The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1413-70542012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the time/temperature binomial on the hydroxymethylfurfural content of floral honeys subjected to heat treatment

Abstract: Hydroxymethylfurfural (HMF) content is internationally recognized for its ability to indicate the freshness or lack of freshness of honey and can be used to judge the processing and storage condition of honey. The objective of the present study was to evaluate the evolution of HMF levels in fresh extracted honeys submitted to different temperatures ranging from 30 to 100º C, during pre-established time intervals (30, 45, 60, 180 and 720 minutes).The test was conducted in floral honey with an initial HMF conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…However, after the burning process of the sugarcane, a common Brazilian stage before harvest, bees use exudate broth to make honey. Due to the heat of burning process, the concentration of furfural becomes high, generating a low price and low quality honey (Ribeiro et al, 2012). Literature evidences present that different types of honey generally are rich in sugar, acids, minerals, aromatic substances, enzymes, vitamins and others (White, 1979), characterized as a potential stuff to alcoholic fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…However, after the burning process of the sugarcane, a common Brazilian stage before harvest, bees use exudate broth to make honey. Due to the heat of burning process, the concentration of furfural becomes high, generating a low price and low quality honey (Ribeiro et al, 2012). Literature evidences present that different types of honey generally are rich in sugar, acids, minerals, aromatic substances, enzymes, vitamins and others (White, 1979), characterized as a potential stuff to alcoholic fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Naturally, honeys contain a small amount of HMF, but which rises under handling, extraction, conditioning and storage operations (TANLEQUE-ALBERTO; JUNA-BORRAS; ESCRICHE, 2019). The HMF content also increases due to heat treatment made by beekeepers to reduce viscosity and prevent crystallization on honey (RIBEIRO et al, 2012).…”
Section: Certifiedmentioning
confidence: 99%
“…Volatile-profile studies have identified chemical markers in monofloral honeys (BARONI et al, 2006;SEISONEN et al, 2015). Changes in volatiles have been reported in honeys subjected to heating, with a consequent alteration of flavor, intensifying the bitter and roasted tastes, and development of the appearance and taste of medicine (CASTRO-VÁZQUEZ et al, 2012;RIBEIRO et al, 2012). KRUŽÍ et al (2017) reported a methodology for investigating volatile compounds in honeys to evaluate the quality and the occurrence of adulterations.…”
Section: Food Technologymentioning
confidence: 99%